1.3 μm InAs/GaAs quantum‐dot laser monolithically grown on Si substrates operating over 100°C. Issue 20 (1st September 2014) - Chen, S.M.; Tang, M.C.; Wu, J.; Jiang, Q.; Dorogan, V.G.; Benamara, M.; Mazur, Y.I.; Salamo, G.J.; Seeds, A.J.; Liu, H.
Abstract : A high‐performance 1.3 μm InAs/GaAs quantum‐dot laser directly grown on Si substrates has been achieved by using InAlAs/GaAs strained‐layer superlattice serving as dislocation filter layers (DFLs). The Si‐based laser achieves lasing operation up to 111°C with a threshold current density of 200 A/cm 2 and an output power exceeding 100 mW at room temperature.